Pola Angin dan Kaitannya terhadap Karakteristik Tinggi Gelombang di Perairan Labuan Bajo, NTT - Prima Aris Wardhani; Supriyatno Widagdo; Viv Djanat Prasita (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2021)
Labuan Bajo waters are marine tourism location that need meteorological and wave height information. The purpose of this research is determining local and regional wind patterns also their connection to wave height characteristics. The prosedure of this research is processing wind data using WR Plot and ArcGIS, then correlation analysis between wind and wave height using SPSS. The results showed that the dominant land breeze blows from South with an average speed of 2.18 knots while the sea breeze blows from Southwest, West, Northwest to North with an average speed of 5.83 knots. Regional wind patterns are influenced by seasonal wind patterns. In the West Season tends blow from West and Northwest with an average speed of 2.49 knots, in the East Season tends to blow from East and Southeast with an average speed of 2.64 knots while in the Transition Season tends to blow from various directions. On a daily, the waves tend to be high at 07:00 with an average of 1.39 m while at 19:00 tend to be low with an average of 0.26 m. Seasonally the highest wave height occurs in the West Season with an average of 1.35 m and the lowest wave height occurs in Transition Season II with an average of 0.79 m. Regional winds and wave heights have a moderate to strong connection in the East Season (R = 0.438-0.639).